2007
DOI: 10.1111/j.1478-3231.2007.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and diabetes mellitus are related to hepatic encephalopathy in patients with liver cirrhosis

Abstract: Malnutrition and diabetes mellitus seem to be related to HE in patients with liver cirrhosis. Nutritional status and insulin resistance might be implicated in the pathogenesis of HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 42 publications
(65 reference statements)
6
75
0
6
Order By: Relevance
“…It is therefore conceivable that deterioration in nutritional status, rather than nutritional status itself, may be of great importance for cognitive dysfunction in patients with liver cirrhosis. Finally, another factor that may, at least in part, explain the differences between the results of the two studies [4,5] is that we also included patients with minimal HE in our analyses [5] whereas as Soros et al [4] included only patients with clinically overt HE in their study.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…It is therefore conceivable that deterioration in nutritional status, rather than nutritional status itself, may be of great importance for cognitive dysfunction in patients with liver cirrhosis. Finally, another factor that may, at least in part, explain the differences between the results of the two studies [4,5] is that we also included patients with minimal HE in our analyses [5] whereas as Soros et al [4] included only patients with clinically overt HE in their study.…”
Section: Introductionmentioning
confidence: 67%
“…Furthermore, in our study, recent weight change was included in the definition of malnutrition [4] whereas in the study of Sörös et al no definition of malnutrition was provided [4] . Interestingly we found that although patients with and without low fat or muscle mass did not differ in number connection A performance times, a recent weight loss was related to longer performance times [81 s (51) vs 54 s (32), P = 0.001] [5] . It is therefore conceivable that deterioration in nutritional status, rather than nutritional status itself, may be of great importance for cognitive dysfunction in patients with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations